UNLOCKING THE FUTURE OF MATERNAL HEALTH: PLATELET INDICES AS PREDICTORS OF PRE-ECLAMPSIA - SHARMA, SONAKSHI; SHARMA, ANOOP; SYAL, GEETIKA GUPTA (International Journal of Current Pharmaceutical Research, 2023)
Objective: Pre-eclampsia is a serious complication of pregnancy, posing significant risks to maternal and fetal health. Predictive indicators for this condition are essential for early diagnosis and management. Platelet indices, including platelet count (PC), platelet distribution width (PDW), mean platelet volume (MPV), and platelet crit (PCT), are potential biomarkers for pre-eclampsia due to their association with coagulation abnormalities. This study aims to investigate the utility of platelet indices in predicting pre-eclampsia. Methods: The study was conducted at Kamla Nehru State Hospital for Mother and Child, Shimla, Himachal Pradesh, from March 1, 2021, to February 28, 2022. Normotensive pregnant women with singleton pregnancies after 20 w of gestation were included, and those with pre-existing conditions were excluded. Platelet indices were measured throughout pregnancy, and patients were categorized based on the development and severity of pre-eclampsia. Data were analyzed using SPSS-PC-25, and statistical tests were performed to determine the significance of platelet index variations. Results: The study reveals significant differences in platelet indices between normotensive and preeclampsia (PE) patients. PE patients exhibited elevated mean platelet volume (MPV), decreased platelet count, and increased platelet distribution width (PDW) compared to normotensive individuals. Notably, MPV increased significantly in PE, preceding blood pressure elevation. Platelet count decreased significantly in severe PE cases. Receiver Operating Characteristic (ROC) curve analysis demonstrated the potential of platelet count and MPV as predictors for PE. These findings underscore the relevance of platelet indices in PE diagnosis and highlight their potential utility as early markers of this hypertensive disorder during pregnancy. Conclusion: Platelet indices, particularly platelet count, MPV, and PDW, hold promise as early markers for predicting and monitoring pre-eclampsia. Monitoring platelet indices alongside blood pressure could aid in assessing the severity and progression of the condition, contributing to improved maternal and fetal outcomes. Further research in this area is warranted to refine predictive models and enhance clinical utility.